1997
DOI: 10.1016/s0014-5793(97)00011-2
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory subunit of protein kinase CK2 is a specific A‐Raf activator

Abstract: Two protein kinases that are involved in proliferation and oncogenesis but so far were thought to be functionally independent are Raf and CK2. The Raf signaling pathway is known to play a critical role in such fundamental biological processes as cellular proliferation and differentiation. Abnormal activation of this pathway is potentially oncogenic. Protein kinase CK2 exhibits enhanced levels in solid human tumors and proliferating tissue. In a two-hybrid screen of a mouse-embryo cDNA library we detected an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 22 publications
6
56
0
2
Order By: Relevance
“…Similar conclusions have been reached using thermosensitive mutants of the CK2a subunit in yeast [12]. Very recently, yeast two-hybrid analysis has been used to demonstrate the interaction of CK2P with A-Raf [13,14] and with mos [15]. Both A-Raf and mos are cytoplasmic oncogene products that have Ser/Thr protein kinase activity that phosphorylate and activate MEK and are therefore involved in the transduction of the stimuli that trigger cell division.…”
Section: Introductionsupporting
confidence: 53%
“…Similar conclusions have been reached using thermosensitive mutants of the CK2a subunit in yeast [12]. Very recently, yeast two-hybrid analysis has been used to demonstrate the interaction of CK2P with A-Raf [13,14] and with mos [15]. Both A-Raf and mos are cytoplasmic oncogene products that have Ser/Thr protein kinase activity that phosphorylate and activate MEK and are therefore involved in the transduction of the stimuli that trigger cell division.…”
Section: Introductionsupporting
confidence: 53%
“…It is possible that the C-terminus of CK2b recognizes a common structural motif of serine/threonine kinases. However, the fact that CK2b interacts specifically with A-Raf (Boldyreff and Issinger, 1997) but not c-Raf (Chen et al, 1997;Hagemann et al, 1997), suggests that kinase interaction with CK2b may require higher specificity. The structure determination of the human Chk1 kinase (Chen et al, 2000) has indicated that the activity of the kinase domain (residues 1-265) of human Chk1 is over 20-fold more active than the full-length Chk1 kinase toward Cdc25C substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast Two-hybrid Screening-Full-length Btk was cloned into pPCH1 (19) and used as a bait. HF7c yeast cells expressing the bait vector were transformed (20) with a human splenic library.…”
Section: Methodsmentioning
confidence: 99%